Soil-associated fungal and prokaryotic diversity influenced by stoniness, depth and vintage in a high-altitude vineyard - Daniela Mezzatesta; Mónica Oyuela Aguilar; Alex Gobbi; Mariano Pistorio; Lars Hestbjerg Hansen; Fernando Buscema; Patricia Piccoli; Frederico Berli (OENO One)
Soil microbes are increasingly recognised as key contributors to wine terroir, playing crucial roles in soil health and nutrient cycling. Fungi and prokaryotes interact with soils, influencing physical and chemical properties and mediating nutrient availability for roots. These microorganisms also impact vine performance and wine quality. Viticulture is expanding to higher elevations due to their cooler temperatures; Mendoza's mountainous regions are of particular interest being, characterised by vineyards with heterogenous soil stoniness. However, the effect of this variability on soil-associated microbial communities remains unclear. This study explores microbial populations (alpha and beta diversity, taxonomical composition, and their relationship with soil physicochemical properties) in soils of contrasting stoniness, at different depths, vintages and sample types. A Malbec vineyard with heterogenous soil stoniness was selected, with two experimental sites 30 m apart containing stony soil (SS; 77 % stoniness) and non-stony soil (NS; 0 % stoniness), respectively, and which were managed identically. Samples were collected from two depths (0.3 m and 0.6 m) during two vintages (2017 and 2018), from bulk and rhizosphere. Amplicon sequencing targeted the V3-V4 region of the 16S rRNA gene (prokaryotes) and the ITS1 region (fungi). Results showed that soil type significantly influences fungal populations, with less effect on prokaryotes. Vintage, reflecting annual changes in weather and viticultural practices, was the most significant factor affecting microbial communities. Depth was particularly important for fungi, while the sampling type (bulk or rhizosphere) had no significant impact on the microbiome within the same soil profile. Certain soil components were found to influence microbial communities: pH affected prokaryotes, while calcareous content specifically influenced the Proteobacteria phylum. Additionally, five fungal orders were more abundant in the stony soils, though some remained unidentified. These findings provide a baseline for understanding microorganisms in contrasting soils types of a high-elevation vineyard, and they highlight the role of microbial diversity in supporting unique soil-plant-environment interactions.